Cell Model of Catecholaminergic Polymorphic Ventricular Tachycardia Reveals Early and Delayed Afterdepolarizations - Kujala, Kirsi (Public Library of Science, 2012)
BACKGROUND: Induced pluripotent stem cells (iPSC) provide means to study the pathophysiology of genetic disorders. Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a malignant inherited ion channel disorder predominantly caused by mutations in the cardiac ryanodine receptor (RyR2). In this study the cellular characteristics of CPVT are investigated and whether the electrophysiological features of this mutation can be mimicked using iPSC -derived cardiomyocytes (CM). METHODOLOGY/PRINCIPAL FINDINGS: Spontaneously beating CMs were differentiated from iPSCs derived from a CPVT patient carrying a P2328S mutation in RyR2 and from two healthy controls. Calcium (Ca(2+)) cycling and electrophysiological properties were studied by Ca(2+) imaging and patch-clamp techniques. Monophasic action potential (MAP) recordings and 24h-ECGs of CPVT-P2328S patients were analyzed for the presence of afterdepolarizations. We found defects in Ca(2+) cycling and electrophysiology in CPVT CMs, reflecting the cardiac phenotype observed in the patients. Catecholaminergic stress led to abnormal Ca(2+) signaling and induced arrhythmias in CPVT CMs. CPVT CMs also displayed reduced sarcoplasmic reticulum (SR) Ca(2+) content, indicating leakage of Ca(2+) from the SR. Patch-clamp recordings of CPVT CMs revealed both delayed afterdepolarizations (DADs) during spontaneous beating and in response to adrenaline and also early afterdepolarizations (EADs) during spontaneous beating, recapitulating the changes seen in MAP and 24h-ECG recordings of patients carrying the same mutation. CONCLUSIONS/SIGNIFICANCE: This cell model shows aberrant Ca(2+) cycling characteristic of CPVT and in addition to DADs it displays EADs. This cell model for CPVT provides a platform to study basic pathology, to screen drugs, and to optimize drug therapy.